Collocational competence and other types of skills and competences: An overview of the state of the art - Targońska, Joanna (Glottodidactica, 2019)
The goal of the article is to examine the dependency between collocational competence and other competences and language skills of a foreign language learner. The paper begins with an explication of the notions of collocation and collocational competence. It further presents the results of an analysis of the relevant research on collocational competence. Based on publications of researchers from all over the world, the research question which has been formulated concerns the dependency between a well developed collocational competence and the level of proficiency in reading, listening, writing and speaking. And conversely, the analysis seeks to find out if the language skills above automatically develop learners’ collocational competence. Finally, the article shows the influence of collocational competence on language reception and production, and discusses some methods which may improve foreign language learners’ collocational competence.